Strange particle production in high-energy electron Proton collision / Zukhaimira binti Zolkapli - Zolkapli, Zukhaimira (2013)
The strangeness total cross sections for ep neutral current deep inelastic scattering (DIS) have been measured using HERA-II data at a center-of-mass energy of s  318 GeV with the ZEUS detector at HERA. The 2003 & 2007 running period data were used with an integrated luminosity of 4.6 pb-1 and compared with ARIADNE Monte Carlo (MC) predictions. The differential production cross-sections of ,  ,    and 0sK were measured in two different kinematic regions,  2DAQ 25 GeV2 for high 2 Q DIS sample and 5  2DAQ 25 GeV2 for low 2 Q DIS sample. The differential cross sections were measured as functions of ( , , ) 0 s    K , ( , , ) 0 T s p   K and 2 Q in the DIS samples. The baryon-antibaryon production asymmetry, defined as ( ) ( )       , and the baryonmeson ratio 0 ( ) s K    were studied and the results were compared with ARIADNE MC prediction. The baryon production process is not well understood yet and therefore it relies much on phenomenological models like the Cluster and String Models. The study on baryon antibaryon rapidity correlation in ep collision can answer these problems. The tracking information from the Micro Vertex Detector (MVD) was used to observe the effect on the strange particles production when using this extra tracking information during the observation of  baryons and 0 s K mesons production at the ZEUS detector, in addition to the Central Tracking Detector.